EFEK LEADER MEMBER EXCHANGE DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR YANG DIMEDIASI OLEH KOMITMEN ORGANISASI - samsul huda; T. KUNCORO T.KUNCORO (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2023)
ABSTRACT Â This study aims to investigate the relationship between Leader-Member Exchange (LMX) and Job Satisfaction on Organizational Citizenship Behavior (OCB), as well as the mediating effect of Organizational Commitment in the relationship. This study was conducted using a quantitative approach through a survey of employees from various industrial sectors. Data were collected using a questionnaire that has been tested for validity and reliability. The results of statistical analysis show that there is a positive and significant relationship between Leader-Member Exchange and Job Satisfaction on Organizational Citizenship Behavior. In addition, Organizational Commitment is proven to mediate the relationship between Leader-Member Exchange and Job Satisfaction on Organizational Citizenship Behavior. This finding indicates that employees who have a good relationship with their superiors (good LMX) and feel satisfied with their jobs tend to show higher levels of Organizational Citizenship Behavior. In addition, high commitment to the organization also plays a role in strengthening the relationship between LMX and Job Satisfaction with Organizational Citizenship Behavior.Keywords: Leader-Member Exchange, Job Satisfaction, Organizational Citizenship Behavior, Organizational Commitment.ABSTRAK Â Penelitian ini bertujuan untuk menginvestigasi hubungan antara Leader-Member Exchange (LMX) dan Kepuasan Kerja terhadap Organizational Citizenship Behavior (OCB), serta pengaruh mediasi Komitmen Organisasi dalam hubungan tersebut. Penelitian ini dilakukan dengan pendekatan kuantitatif melalui survei kepada karyawan dari berbagai sektor industri. Data dikumpulkan menggunakan kuesioner yang telah teruji validitas dan reliabilitasnya. Hasil analisis statistik menunjukkan bahwa terdapat hubungan positif dan signifikan antara Leader-Member Exchange dan Kepuasan Kerja terhadap Organizational Citizenship Behavior. Selain itu, Komitmen Organisasi terbukti memediasi hubungan antara Leader-Member Exchange dan Kepuasan Kerja terhadap Organizational Citizenship Behavior. Temuan ini mengindikasikan bahwa karyawan yang memiliki hubungan yang baik dengan atasan (LMX yang baik) dan merasa puas dengan pekerjaan mereka cenderung menunjukkan tingkat Organizational Citizenship Behavior yang lebih tinggi. Selain itu, komitmen yang tinggi terhadap organisasi juga berperan dalam memperkuat hubungan antara LMX dan Kepuasan Kerja dengan Organizational Citizenship Behavior.Â Kata Kunci: Leader-Member Exchange, Kepuasan Kerja, Organizational Citizenship Behavior, Komitmen